Managing school-based conflicts as a social factor influencing educational environments: A case study approach - Mufidah, Diroyatul (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Conflict in schools often arises from interactions among various parties with differing goals, values, or interests. This study aims to analyze the implementation of conflict management. Methods: The research method used is qualitative with a case study approach. Data collection techniques include interviews, observations, and document analysis. Findings: This study found that conflicts at the school involved students, teachers, educational staff, and even parents. The types of conflict identified include interpersonal conflict, intergroup conflict, and structural conflict. The causes of conflict include differences in values and goals, as well as a lack of effective communication. In resolving these conflicts, the school implements various conflict management approaches such as collaboration, compromise, and accommodation. These implementations are supported by internal policies and coordination efforts led by the principal, teachers, and other relevant stakeholders. The findings indicate that appropriate conflict management approaches can foster a conducive learning environment, enhance communication quality, and strengthen collaboration among school stakeholders. Conclusion: Conflicts in this study arise from miscommunication, misunderstandings, differing perspectives, and lack of discipline, involving various types such as interpersonal, constructive, and destructive conflicts. While conflict management has been effectively implemented through deliberation, mediation, and compromise, it remains informal, undocumented, and not fully aligned with the POAC framework. Novelty/Originality of this article: This study contributes to the development of both theory and practice in conflict management within educational institutions. Through the implementation of effective conflict management, negative conflicts can be minimized, while positive conflicts can be leveraged to enhance creativity and innovation in the learning process.